Comparative assessment of the epidemic state of tuberculosis before and during the war in Ukraine - I. O. Novozhylova; O. P. Nedospasova; A. M. Prykhodko; I. V. Bushura (Civic Union "Communicable Diseases Intensive Care Association", 2024)
BACKGROUND. The war has a negative impact on patient care and the efficiency of the health care system; access to medical care is limited, coverage of preventive examinations and detection of tuberculosis (TB) are deteriorating. There is a threat of exacerbation of the epidemic situation with TB in Ukraine. OBJECTIVE. To assess the epidemic situation with TB during the war in Ukraine. MATERIALS AND METHODS. Comparison of data from the Ministry of health on TB (epidemiological indicators and indicators on detection, diagnosis and prevention) in the pre-war (2018-2021) and war (2022-2023) periods. RESULTS. The following were revealed: 1) a positive trend towards a decrease in epidemiological indicators of TB in 2018-2020, which slowed down in 2021 due to the COVID-19 pandemic, and a negative trend towards an increase in almost all indicators of TB incidence, separate indicators of mortality from TB and its prevalence in 2022-2023; 2) significant increase in the incidence of TB among contacts and children; 3) increase by ⅓-. of mortality from TB in certain regions; 4) correlation between regional rates of morbidity, mortality and prevalence of TB. In 2018-2023, the following decreased: fluorography examination, tuberculin diagnostics, detection of TB during preventive examinations (by 2-4 times), preventive vaccinations for children of the first year of life, detection of newly diagnosed and recurrent TB by smear, preventive treatment in contacts. CONCLUSIONS. Incidence is a marker of response to negative external factors and the main criterion for assessing the epidemic state of TB during the war. Fluorography examination, tuberculin diagnostics, detection of TB during professional examinations, preventive vaccinations for children of the first year of life, detection of newly diagnosed and recurrent TB by smear, preventive treatment of contacts are the main criteria for evaluating the activity of the anti-TB service during the wartime, since they are the first to significantly respond to the challenges of war.